Development of novel vaccine vectors: Chimpanzee adenoviral vectors. Issue 7 (3rd July 2018) - Guo, Jingao; Mondal, Moumita; Zhou, Dongming
ABSTRACT: Adenoviral vector has been employed as one of the most efficient means against infectious diseases and cancer. It can be genetically modified and armed with foreign antigens to elicit specific antibody responses and T cell responses in hosts as well as engineered to induce apoptosis in cancer cells. The chimpanzee adenovirus-based vector is one kind of novel vaccine carriers whose unique features and non-reactivity to pre-existing human adenovirus neutralizing antibodies makes it an outstanding candidate for vaccine research and development. Here, we review the different strategies for constructing chimpanzee adenoviral vectors and their applications in recent clinical trials and also discuss the oncolytic virotherapy and immunotherapy based on chimpanzee adenoviral vectors.